Design a Phinisi-Type Tourist Ship to Increase Tourist Interest in Vacationing at Taka Bonerate National Park - Suardi; Adhy Rahmat; Wira Setiawan; Muhammad Uswah Pawara; Alamsyah Pawara; Andi Mursid Nugraha Arifuddin; Taufik Hidayat (International Journal of Marine Engineering Innovation and Research, 2023)
Tourism ship with the Phinisi ship concept for the Selayar Islands tourist area are designed to increase the number of tourist attractions in the area. With beach tourism destinations and coral reefs, the Selayar region is very possible to become an alternative tourist destination in Indonesia besides Bunaken, Raja Ampat, Labuan Bajo, and the island of Bali. This ship is designed with wood materials and carries the theme of the traditional Phinisi ship which is the hallmark of ships made by the Bugis-Makassar tribe since 3000 years ago and has been recognized by UNESCO as one of the world's cultural heritage (Art of Boatbuilding in South Sulawesi). This study aims to obtain a tourist ship design that can be an attraction for tourists to vacation in the Selayar Islands. The method used in this study is the parent ship design approach method, this method is very commonly used in the ship design process, namely by using a comparison ship as a reference in the design of a new ship. The main ship dimensions obtained from this research are Loa = 26 m, B = 6.1 m, H = 2.48 m, T = 1.6 m, Vs (max) = 10 Knots, and Crew = 6 persons. The room on the ship is made like a classy hotel room and other services can pamper tourists.